2013
DOI: 10.1007/s10886-013-0284-1
|View full text |Cite
|
Sign up to set email alerts
|

Epicuticular Compounds of Drosophila subquinaria and D. recens: Identification, Quantification, and Their Role in Female Mate Choice

Abstract: The epicuticle of various Drosophila species consists of long-chain cuticular hydrocarbons (CHCs) and their derivatives that play a role in waterproofing and a dynamic means of chemical communication. Here, via gas chromatography and mass spectrometry, we identified and quantified the epicuticular composition of D. recens and D. subquinaria, two closely related species that show a pattern of reproductive character displacement in nature. Twenty-four compounds were identified with the most abundant, 11-cis-Vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 61 publications
4
50
0
Order By: Relevance
“…Branch lengths are proportional to evolutionary time. *Evidence for TAG-expression is based on Curtis et al, 2013. DOI: http://dx.doi.org/10.7554/eLife.01751.003
10.7554/eLife.01751.004Figure 1—figure supplement 1.Representative UV-LDI spectra from distantly related drosophilids in the Drosophila subgenus.Signals corresponding to sex-specific TAGs (in red) are identified based on the exact mass measurements, predicted elemental composition, and number of double bonds. Labeled signals correspond to potassiated molecules [M + K] + .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Branch lengths are proportional to evolutionary time. *Evidence for TAG-expression is based on Curtis et al, 2013. DOI: http://dx.doi.org/10.7554/eLife.01751.003
10.7554/eLife.01751.004Figure 1—figure supplement 1.Representative UV-LDI spectra from distantly related drosophilids in the Drosophila subgenus.Signals corresponding to sex-specific TAGs (in red) are identified based on the exact mass measurements, predicted elemental composition, and number of double bonds. Labeled signals correspond to potassiated molecules [M + K] + .
…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of Sophophora and Drosophila flies identified alkanes, alkenes, and oxygen-modified hydrocarbons as the major lipids used as pheromones (Jallon and David, 1987; Greenspan and Ferveur, 2000). Recently, triacylglycerides (TAGs), which are normally found in the fat bodies and used for energy storage, were observed on the cuticles of flies from the Drosophila repleta and Drosophila quinaria groups (Yew et al, 2011; Curtis et al, 2013). However, almost nothing is known about the structure, chemical diversity, conserved expression, and functional roles of these exogenously secreted TAGs.…”
Section: Introductionmentioning
confidence: 99%
“…In rock-pool beetles (Ochthebius urbanelliae), reinforcement creates isolation between allopatric and sympatric populations, so sympatric populations mate with one another but will not mate with allopatric populations (Porretta and Urbanelli 2012). In Drosophila subquinaria, sympatric females reject allopatric males on the basis of epicuticular compounds (Jaenike et al 2006;Curtis et al 2013;Giglio and Dyer 2013;Dyer et al 2014), while in Drosophila serrata, allopatric females reject sympatric males (Higgie and Blows 2008). Our results are most similar to those for walking stick insects (Nosil et al 2003), in which sympatric females preferred native males over males from foreign pop- ulations regardless of whether the foreign males were from sympatric or allopatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes may allow males to select for or against females based on their previous exposure to desiccation stress, and/or allow females to signal enhanced desiccation tolerance. In addition, in males the importance of CHCs as sexual displays that affect attractiveness to females has been well established in multiple Drosophila species (e.g., Chenoweth and Blows, 2005;Van Homrigh et al, 2007;Curtis et al, 2013;Chung et al, 2014;Dyer et al, 2014). Sexual selection on CHCs may therefore be antagonistic to desiccation hardening responses, as well as longer-term adaptation to desiccation stress (e.g., Kwan and Rundle, 2010), potentially explaining the reduced response in males in both of these contexts.…”
Section: Tablementioning
confidence: 99%